2020
DOI: 10.7759/cureus.10423
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Use of Cloth Masks: A Scoping Review

Abstract: During the coronavirus disease 2019 (COVID-19) pandemic, there has been a global shortage of personal protective equipment (PPE). In this setting, cloth masks may play an important role in limiting disease transmission; however, current literature on the use of cloth masks remains inconclusive. This review aims to integrate current studies and guidelines to determine the efficacy and use of cloth masks in healthcare settings and/or the community. Evidence-based suggestions on the most effective use of cloth ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 17 publications
1
19
1
1
Order By: Relevance
“…This evaluation is supported by the likelihood of observing reduced particle counts by random variation, as determined by Tukey's Honest Significant Difference post-hoc tests in the enclosed box experiments, where the N95T was significantly different in all positions, and the SewnF was different in all particle sizes but the 5-10 μm size bin. This result differs from previous studies that had found that surgical masks were generally superior to cotton, homemade counterparts, though these studies do not sample using 3D printed models and use different particles for measurement [28,45,46]. Depending on the conformation of each facemask relative to the face geometry, gaps resulted from fitting the facemask, and these gaps opened low-pressure outlets for the redirection of particles, as easily visualized by the change in bar height between facemask types across the rows of Cloth facemasks permit more particles to exit at the top of the facemask on our face model, but this effect could be mitigated through the use of a nose clip or filter.…”
Section: Discussioncontrasting
confidence: 94%
“…This evaluation is supported by the likelihood of observing reduced particle counts by random variation, as determined by Tukey's Honest Significant Difference post-hoc tests in the enclosed box experiments, where the N95T was significantly different in all positions, and the SewnF was different in all particle sizes but the 5-10 μm size bin. This result differs from previous studies that had found that surgical masks were generally superior to cotton, homemade counterparts, though these studies do not sample using 3D printed models and use different particles for measurement [28,45,46]. Depending on the conformation of each facemask relative to the face geometry, gaps resulted from fitting the facemask, and these gaps opened low-pressure outlets for the redirection of particles, as easily visualized by the change in bar height between facemask types across the rows of Cloth facemasks permit more particles to exit at the top of the facemask on our face model, but this effect could be mitigated through the use of a nose clip or filter.…”
Section: Discussioncontrasting
confidence: 94%
“…While efficacy (performance in controlled or ideal conditions) and effectiveness (performance in usual or realworld conditions) are not synonymous [450,509], a large consensus and a growing body of literature have moved forward the uptake of community masking as part of comprehensive NPI bundles or "policy packages" aimed at preventing infections caused by respiratory viruses including SARS-CoV-2 [55, 58,261,262,295,464,508,[510][511][512][513][514][515][516]. Importantly, a fact undergirding community mask wearing during the pandemic is the risk of transmission, not only from symptomatic individuals, but also from presymptomatic and asymptomatic individuals (discussed in section 3).…”
Section: Toward a Multidisciplinary Agreement On Actionable Terminologymentioning
confidence: 99%
“…A systematic review conducted by Jain et al (36) showed that cloth masks have protective efficacy, but that penetration of cloth masks is higher than that of surgical masks and N95 respirators N95. Cloth masks may be used in low risk areas and by the community if there are no surgical masks available.…”
Section: Cloth Masksmentioning
confidence: 99%